Edukasi Pentingnya Vaksinasi Covid-19 di Dusun Waralohi Kab. Seram Bagian Barat - Mohammad Dahlan Sely; Wiwi Rumaolat; Abdul Rijali Lapodi (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
Vaccination is the process of giving vaccines by injection or dripping into the mouth to increase the production of antibodies to ward off certain diseases. Vaccination for Covid-19 is one way to prevent transmission of Covid-19. Lack of outreach and education will program Covid-19 to be one of the factors causing people to be afraid of being vaccinated. Community service activities aim to provide education and outreach about the importance of stopping Covid-19. In addition, it also has a specific purpose for a disease so that if one day we are exposed to the disease, the antibodies in our body will prevent or reduce the risk of getting sick. Lack of attention to health protocols and understanding of vaccines makes residents of Waralohi, Kab. West Seram considers this COVID-19 as an ordinary outbreak. Therefore, education about vaccines was held in Waralohi Hamlet, Kab. West Seram. This education was chosen because it can provide knowledge, especially about vaccines. Like things to do before and after vaccination. This activity can be written as one of our concerns for the residents of Waralohi Kab. West Seram during the COVID-19 Pandemic.